2013
DOI: 10.1016/s1001-9294(13)60040-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Programmed Death-ligand 1 and Clinicopathological Characteristics in Non-small Cell Lung Cancer Patients

Abstract: PD-L1, secreted from TAM, might induce cancer cells apoptosis, and decrease lymph node metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…PD‐L1 that is expressed in cancer cells could specifically bind to the receptor (PD‐1) on the surface of activated T cells in the tumor microenvironment and transmit negative regulatory signals to inhibit T cell activation, proliferation or cytokine secretion [20,21]. The rates of PD‐L1 expression are quite different (25–65%) in non‐small‐cell lung cancer as determined by immunohistochemistry [22–24]. The difference may be a result of various factors, such as the regional specificity of the tumor, differences in the experimental method or criteria for judgment, or the pathological state of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…PD‐L1 that is expressed in cancer cells could specifically bind to the receptor (PD‐1) on the surface of activated T cells in the tumor microenvironment and transmit negative regulatory signals to inhibit T cell activation, proliferation or cytokine secretion [20,21]. The rates of PD‐L1 expression are quite different (25–65%) in non‐small‐cell lung cancer as determined by immunohistochemistry [22–24]. The difference may be a result of various factors, such as the regional specificity of the tumor, differences in the experimental method or criteria for judgment, or the pathological state of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 expression has been reported to be associated with vascular invasion and higher-grade differentiation but improved relapse free survival [45]. PD-L1 expression is associated with increased macrophages [47], increased dendritic cells [50] and increased inflammatory infiltrate [46]. In contrast, one study found PD-L1 expression was inversely related to TILs [51].…”
Section: Co-inhibitory Interactionsmentioning
confidence: 99%
“…Recently, it is reported that PD-L1 was expressed in 19.6% to 65.3% of NSCLC, 7,[11][12][13][14] and that EGFR mutation status was associated with PD-L1 expression. 15,16 More interestingly, PD-L1 positive patients treated with EGFR-TKIs have higher response rate and longer time to progression (TTP) compared with PD-L1 negative patients.…”
mentioning
confidence: 99%